Brazil after Bolsonaro: The comeback of Lula da Silva - da Silva, Sven (European Review of Latin American and Caribbean Studies, 2025)
Brazil after Bolsonaro: The comeback of Lula da Silva, edited by Richard Bourne, Routledge, 2024